2014
DOI: 10.7314/apjcp.2014.15.13.5437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PLCE1 Gene Silencing by RNA Interference on Cell Cycling and Apoptosis in Esophageal Carcinoma Cells

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most malignancies with a poor prognosis. The phospholipase Cε gene (PLCE1) encodes a novel ras-related protein effector mediating the effects of R-Ras on the actin cytoskeleton and membrane protrusion. However, molecular mechanisms pertinent to ESCC are unclear. We therefore designed PLCE1-special small interfering RNA and transfected to esophageal squamous cell (EC) 9706 cells to investigat the effects of PLCE1 gene silencing on the cell cycle and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Recent studies have shown that PLCE1 may serve a critical function in the carcinogenesis process of esophageal and gastric cancers (Yu et al, 2014;Zhao et al, 2014) and have identified its involvement in various cancers, such as carcinoma of bladder (Ou et al, 2010), colorectal (Wang et al, 2012b), head and neck (Bourguignon et al, 2006), and skin (Bai et al, 2004) cancers. In previous studies of esophageal and gastric cancers, increased PLCE1 expression was significantly correlated with invasion depth, lymph node metastasis, and histologic grade.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that PLCE1 may serve a critical function in the carcinogenesis process of esophageal and gastric cancers (Yu et al, 2014;Zhao et al, 2014) and have identified its involvement in various cancers, such as carcinoma of bladder (Ou et al, 2010), colorectal (Wang et al, 2012b), head and neck (Bourguignon et al, 2006), and skin (Bai et al, 2004) cancers. In previous studies of esophageal and gastric cancers, increased PLCE1 expression was significantly correlated with invasion depth, lymph node metastasis, and histologic grade.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of patients were found with the advanced period of esophageal cancer when diagnosed, with unfavorable prognosis, about 6~8 months of natural course, 5%~7% five-year survival rate (; Liu et al, 2014;Mai et al, 2014;Zhao et al, 2014;Jiang et al, 2014;Wang et al, 2014;Stefani et al, 2014). Additionally, even though patients accepted surgical treatment, there still exists postoperative recurrence and metastasis in nearly 90% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…PLCE1 encodes the phospholipase C epsilon 1 (PLCe1) that catalyses the hydrolysis of phosphatidylinositol-4, 5-bisphosphate into the secondary messengers inositol 1, 4, 5-trisphosphate and diacylglycerol (DAG), which participate in cell growth, differentiation and gene expression. Recent studies have reported that PLCE1 plays crucial roles in carcinogenesis (Zhao et al, 2014) several types of cancer, and it has been a hot topic to investigate and study the relationship between PLCE1 rs2274223 polymorphism and susceptibility to esophageal cancer (Yu et al, 2013). Numerous case-control studies and cohort studies on the association of PLCE1 rs2274223 polymorphisms with esophageal cancer susceptibility have been conducted.…”
Section: Introductionmentioning
confidence: 99%